Concept of Sarat Ritucharya- A Practical Approach - Yashas U,; P.Sudhakar Reddy,; Beena MD, (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda- The science of life, has two aims, firstly it aimed at to preserve and protect the health of a healthy individual and secondly to cure the disease. As Ayurveda gives first priority to the preventive aspects to preserve and protect the health, it described preventive principles under the heading of Swasthavritta. Swasthavritta classically includes Dinacharya, Nishacharya and Ritucharya. These Charyas if followed properly, brings the balance in Thridosha (Vata, Pitta & Kapha) and thus maintains the Samadoshavastha (Homeostasis of humours/health). Thidoshas are always dynamic in nature, especially during seasonal variation. Adaptation to each Ritu is always a challenging to human beings, more in modern era, where people are running with mechanical life and exposing to pollutants. Ayurveda beautifully described Ritucharya prescription to be followed to bring balance in Tridoshavastha and also prevent morbid matter accumulation. There are six Rutus namely Sisira, Vasantha, Greeshma, Varsha, Sharat & Hemantha, among these, Sharat Ritu (mid-September - mid November) comes under the Visargakala constituting of Ashwini and Karthika Masa. In this Ritu physiologically Pitta undergoes Prakopa, if not followed Ritucharya properly, the Pitta will get vitiate and causes Pitta related diseases. In this article an honest attempt has been made to gather information regarding Sarat ritucahrya from all possible literature from Ayurvedic classics with practical aspects.